2017
DOI: 10.1371/journal.pone.0183826
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressant prescription pattern and trend in kidney transplantation: A multicenter study in Korea

Abstract: BackgroundThe actual prescription pattern of immunosuppressive agents in kidney transplantation is unclear.MethodsWe investigated the pattern and trend of immunosuppressive treatment for kidney transplant patients in South Korea. A total of 636 patients at nine transplant centers were enrolled and followed for one year. We reviewed medical records and evaluated induction therapy, as well as the changing pattern and cause of maintenance therapy.ResultsMost patients (n = 621, 97.6%) received induction therapy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…This trend reflected a tendency to lower the intensity of immunosuppressant treatment in the elderly patients because of the high frequency of immunosuppression-related complications. 21 The incidence of BPAR did not differ between the elderly and young patients in the LDKT and DDKT groups. However, high pre-transplant sensitization showed a differential impact on the elderly and young populations.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This trend reflected a tendency to lower the intensity of immunosuppressant treatment in the elderly patients because of the high frequency of immunosuppression-related complications. 21 The incidence of BPAR did not differ between the elderly and young patients in the LDKT and DDKT groups. However, high pre-transplant sensitization showed a differential impact on the elderly and young populations.…”
Section: Discussionmentioning
confidence: 81%
“…In regard to immune suppression regimen, the proportion of patients treated with cyclosporin instead of tacrolimus was higher in the elderly‐LDKT group. This trend reflected a tendency to lower the intensity of immunosuppressant treatment in the elderly patients because of the high frequency of immunosuppression‐related complications …”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations in drug metabolism have been reported for African Americans in the United States, as well as the possibility of the variation in a gene involved in the coagulation cascade contributing to increased acute rejection in African Americans . In contrast, studies of Asian recipients have suggested differences in the pharmacokinetics of mycophenolate compared to Caucasian patients given similar doses …”
Section: Discussionmentioning
confidence: 99%
“…Los inmunosupresores y antihipertensivos empleados en este tipo de pacientes tienen el objetivo de prevenir y tratar el rechazo agudo y evitar la lesión crónica del injerto, minimizando los efectos adversos 46,47 . Un estudio realizado en México encontró que los inhibidores de calcineurina tienen una relación con la inflamación gingival o con el daño periodontal, mayormente la Ciclosporina A 48,49 ; este hallazgo es semejante al del presente estudio.…”
Section: Discussionunclassified